Evaluation of Foreign Distributors : Small/ Medium Size Entreprises - Valachovic, Jergus (2013)
This study is building on the case of SME CVK situated in Luleå. The company is manufacturing innovative vibration measuring instrument measuring vibrations on human body. The company is active mainly on the international market through their network of foreign distributors. These distributors are performing differently; some of them are selling better some worse. The purpose of the study is to gain deeper understanding in the area of distributor‟s evaluation, to understand the factors differentiating distributors‟ performance. Two research questions have been formulated; first one was dealing with the factors that were connected directly to the particular distributor whereas the topic of the second research question was mainly analyzing the relationship between CVK and every distributor.Six distributors have been analyzed according to number of aspects that was picked up from the study of literature. Number of different models was considered and out of those a theoretical framework was created, comprising two main groups of aspects. First group ought to answer the first research question whereas the aspects from the second group were used to answer the second research question.The most important factors seem to be the external environment around the distributor‟s company and the potential of the market. This market is very specific so it is important that manufacturer formulates its expectations in accordance with the power of the market. It is also shown that the company needs to have knowledge of the industry and previous experiences with the product. Furthermore, financial stability and good reputation appear to be important as well. Commitment is also a good sign of well performing distributor. If the distributor is active, interested in products, and ask a lot of questions it is also likely to sell more. Validerat; 20130613 (global_studentproject_submitter)